Finding Global Balance : Common Ground Between the Worlds of Development and Faith - Marshall, Katherine (Washington, DC: World Bank, 2012)
This book relates the latest chapter in the story of a remarkable partnership between the worlds of faith and development, launched in 1998 by Jim Wolfensohn and then Archbishop of Canterbury, George Carey, when they convened a meeting of faith and development leaders in Lambeth Palace. The intervening years have seen the growth and enhancement of a network of world faith and development leaders who share a common passion to eradicate global poverty, extend social justice and ensure global security for all of the world's people. Periodically this group of leaders gathers together to debate issues of common concern and global significance. The most recent meeting took place in Dublin, Ireland in January 2005. Debates over two days were rich and provocative, examining issues ranging from the recent Asian tsunami, to HIV/AIDS, gender and youth, and the roots of conflict, all viewed through the lens of equity. References to the ethical dimensions of poverty alleviation and the need for a strong moral underpinning as a foundation for equitable and sustainable development lay at the heart of every session. The uniqueness of this partnership is the fresh perspective it offers on critical development issues and the opportunity for faith leaders and development leaders to seek new avenues for collaboration. The book tells the story of this partnership, within the context of the Dublin meeting. It draws primarily on background materials prepared for the meeting and on discussions during the meeting itself.